PTU-250 Predictive factors for incisional hernia at the extraction site after laparoscopic right colectomy for cancer: a large observational study. (22nd June 2015) - Stefan, S; Shamali, A; Pares, D; Flashman, K; O'Leary, D; Conti, J; Senapati, A; Parvaiz, A; Khan, J
Abstract : Introduction: Incisional hernia at the extraction site (ESIH) is one of the common complications after laparoscopic colorectal resection. Information about the risk factors for ESIH could be useful in order to introduce preventive measures. The aim of this study is to evaluate the prevalence and the risk factors for ESIH in a large cohort study. Method: We reviewed a prospectively collected database from November 2006 to October 2013 including all patients who underwent elective laparoscopic right or extended right colectomy for cancer. Demographics, clinical data, length and site of extraction were included. All of patients have been followed up with a minimum of one year with CT scan. Multivariate regression analysis was performed to identify risk factors for ESIH in these patients. Results: A total of 292 patients were included. During a median follow-up of 42 months (range 12–96), 20 patients (6.8%) developed ESIH. The rate of ESIH was higher in the patients with umbilical midline incision (9.1%) than other sites (3.4%). However this difference was not statistically significant (p = 0.062). In the multivariable analysis a BMI > 30 (odds ratio [OR] = 3.76, 95% confidence interval CI 1.39–10.15; p = 0.009) and an incision length more than 5 cm (OR: 2.86, 95% CI: 1.077–7.60; p = 0.035) were significant predicting variables contributing to the risk of developing ESIH. Conclusion: This study identified several factors that could be useful to introduce preventive measures in high risk patients such as mesh closure, reducing the length of incision by intracorporeal anastomosis and non-umbilical extraction site in high-risk patients. Disclosure of interest: None Declared.